A Coordinated Clinical Center for Young Onset Colorectal Cancer. (17th June 2021) - Mendelsohn, Robin; Palmaira, Randze Lerie; Lumish, Melissa; Bacani, Joseph; Krishnan, Asha; Weiss, Jill; Semler, Rosemary; Casson, Anne; Arkema, Ashley; Carter, Jeanne; Nelson, Christian; Mulhall, John; et al.
Abstract : The increase in young onset colorectal cancer and the complex care needs of young cancer patients spurred the development of the Center for Young Onset Colorectal Cancer at the Memorial Sloan Kettering Cancer Center. This article describes the lessons of the first 2 years at the Center, including development of the program and specific services provided.